Ethnic Media: Breaking the Ghetto Politics - Gouliamos, Kosta (Études helléniques / Hellenic Studies, 1995)
The paper examines the notion of life world and correlates it to the politics of multiculturalism. It further considers multiculturalism to be a postcolonial condition reinforced by corporate capitalism, the politics of biculturalism and various exotic (ethnic) events that lead to acculturation and a politicization. Within this postcolonial logic, the ethnic media operate as a totem that inscribes the dominant discourse (metropolitan and peripheral). Taking into account the Greek-Canadian case, the paper demonstrates the process as well as the practices by which the ethnic media transmit a consciousness that affirms dominant cultural paradigms. Finally, the paper provides an exit from the ghetto politics of multiculturalism by proposing a synthesis of counter-hegemonic politics and creation of a transcultural federation.